An Isothermal Titration Calorimetry Study on the Binding of Four Volatile General Anesthetics to the Hydrophobic Core of a Four-α-Helix Bundle Protein - Zhang, Tao (Biophysical Society, 2003)
A molecular understanding of volatile anesthetic mechanisms of action will require structural descriptions of anesthetic-protein complexes. Previous work has demonstrated that the halogenated alkane volatile anesthetics halothane and chloroform bind to the hydrophobic core of the four-α-helix bundle (Aα(2)-L38M)(2) (Johansson et al., 2000, 2003). This study shows that the halogenated ether anesthetics isoflurane, sevoflurane, and enflurane are also bound to the hydrophobic core of the four-α-helix bundle, using isothermal titration calorimetry. Isoflurane and sevoflurane both bound to the four-α-helix bundle with K(d) values of 140 ± 10 μM, whereas enflurane bound with a K(d) value of 240 ± 10 μM. The ΔH° values associated with isoflurane, sevoflurane, and enflurane binding were –7.7 ± 0.1 kcal/mol, −8.2 ± 0.2 kcal/mol, and –7.2 ± 0.1 kcal/mol, respectively. The ΔS° values accompanying isoflurane, sevoflurane, and enflurane binding were −8.5 cal/mol K, −10.4 cal/mol K, and −8.0 cal/mol K, respectively. The results indicate that the hydrophobic core of (Aα(2)-L38M)(2) is able to accommodate three modern ether anesthetics with K(d) values that approximate their clinical EC(50) values. The ΔH° values point to the importance of polar interactions for volatile general anesthetic binding, and suggest that hydrogen bonding to the ether oxygens may be operative.